Knowledge contribution within the Eyre Peninsula's fishing industry in Australia. Issue 2 (4th March 2022) - Quartey, Samuel Howard; Wells, Sam
ABSTRACT: Knowledge contribution has yielded extensive explanations regarding experts' ability to share and combine new ideas, information, and knowledge for collective use and benefit. While the notion of knowledge contribution has largely benefited virtual, electronic and online communities and organisations, it is less appropriate in real organisations. This paper explores knowledge contribution within the Eyre Peninsula's fishing industry in Australia, from a social capital perspective. Qualitative data were obtained from in-depth interviews with 54 value chain actors across the industry. The findings suggest that knowledge contribution is inconceivable without social processes. Formal and informal social processes explain knowledge contribution within the Eyre Peninsula's fishing industry. A stronger emphasis on informal social processes foster tacit knowledge contribution, while formal social processes enhance explicit knowledge contribution. The paper advances social capital theory by showing that informal and formal social processes can develop relational practices and social structures that foster knowledge combination.